Safety of thromboprophylaxis after oncologic head and neck surgery. Study of 1018 patients. Issue 10 (20th November 2012) - Gavriel, Haim; Thompson, Evan; Kleid, Stephen; Chan, SorWay; Sizeland, Andrew
<x xml:space="preserve">Abstract</x> Background Deep venous thrombosis (DVT) and pulmonary embolism (PE) are significantly reduced with appropriate use of thromboprophylaxis and scarcely evaluated in patients undergoing oncologic head and neck surgery (OHNS). Methods A retrospective study on 1018 patients who underwent oncologic head and neck surgery. The records of patients with venous thromboembolism (VTE) or postoperative bleeding were reviewed for the cancer grading, management, previous known coagulopathy, anticoagulation, and general demographics. Results Of a total of 1018 patients undergoing oncologic head and neck surgery, 450 patients had no chemoprophylaxis and 568 received it. The rate of a VTE event in our cohort was 0%. Twelve patients presented with hematoma or bleeding from the surgical site, 11 in the group that received chemoprophylaxis (p = .006). Conclusions Our analysis shows no benefit from chemoprophylaxis in oncologic head and neck surgery patients, with no VTE events. Our analysis shows higher rates of morbid side effects from using chemoprophylaxis, and we therefore conclude that chemoprophylaxis should not be routinely used. © 2012 Wiley Periodicals, Inc. Head Neck 35: 1410–1414, 2013